Human Development and Its Effects on Economic Growth and Development - Appiah, Michael; Amoasi, Richard; Frowne, Doreen Idan (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2019)
The focus of the current study is to empirically examine the impact of Human Development on Economic Growth and Development in African countries, between 1990 and 2015. The key findings and results of the study suggested the existence of a positive and significant impact of human development on economic growth and development in Africa. The study employed Human Development Index as the main variable of interest with GDP considered as the dependent variable with inflation, capital, investment and labor as control variables. The study also came out with the findings that Labour and foreign aid also have a positive and significant relationship with growth as recorded by most researchers. It was recommended that more efforts should be placed on developing human capacities in all areas.Keywords:Human development, economic growth, random effect, fixed effect* Department of Management Science & Engineering, School of Finance and Economics, Jiangsu University, 301 Xuefu Road, Zhenjiang, Jiangsu, 212013, P.R. China** Department of Marketing, Koforidua Technical University, P. O. Box Kf 98, Koforidua, Ghana https://doi.org/10.21632/irjbs.12.2.101-109